Neurological soft signs (NSS) and gray matter volume (GMV) in first-episode psychosis: an analysis of NSS motor subscores - Quispe Escudero, David; Herold, Christina; Kong, Li; Schröder, Johannes (Psychiatry research. Neuroimaging, 2020)
We aimed to study the correlations between gray matter volume and the motor subscores of NSS in first-episode psychosis patients with both, whole brain and region of interest analyses. The structural MRIs of 81 first-episode psychosis patients were analyzed by using voxel-based morphometry (VBM) for SPM. NSS were assessed using the Heidelberg scale. Significant decreases of gray matter volume were correlated to high NSS total scores and, more specifically, frontal, subcortical and cerebellar areas were significantly correlated with increased scores of the subscores Motor Coordination (MoCo) and Complex Motor Tasks (CMT). When applying a stricter statistical correction, only the frontal gyrus and caudate nucleus survived for MoCo; whereas the precentral and superior frontal gyri survived for CMT. When doing regional analyses, using as masks the structures deemed as significant by the whole brain analyses and applying the FWE-correction, the superior frontal gyrus, thalamus and caudate nucleus correlated negatively with MoCo; and the precentral and superior frontal gyri, thalamus and caudate nucleus showed inverse correlations with CMT. These results suggest that cerebral cortex, subcortical structures (thalamus and striatum) and cerebellum are inversely correlated to both motor NSS subscores, the first time a study describes this relationship for all the relevant structures simultaneously. For its part, ROI proves to be effective demonstrating that subcortical structures (thalamus and caudate) are the most affected by motor NSS.